2013
DOI: 10.1085/jgp.201210861
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16F (Anoctamin 6), an anion channel of delayed Ca2+ activation

Abstract: Members of the TMEM16 (Anoctamin) family of membrane proteins have been shown to be essential constituents of the Ca2+-activated Cl− channel (CaCC) in many cell types. In this study, we have investigated the electrophysiological properties of mouse TMEM16F. Heterologous expression of TMEM16F in HEK293 cells resulted in plasma membrane localization and an outwardly rectifying ICl,Ca that was activated with a delay of several minutes. Furthermore, a significant Na+ current was activated, and the two permeabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
140
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(167 citation statements)
references
References 61 publications
22
140
4
Order By: Relevance
“…For ANO6/ TMEM16F, a similar role has been described recently (Juul et al 2014;Ousingsawat et al 2015;Sirianant et al 2015). ANO6 is a Ca 2+ -activated phospholipid scramblase that may also operate as a Ca 2+ -activated Cl − or nonselective ion channel (Grubb et al 2013;Kunzelmann et al 2014;Shimizu et al 2013;Suzuki et al 2010;Tian et al 2012;Yang et al 2012). We found that ANO6 is activated by hypotonic cell swelling, or, alternatively, controls the activity of VRAC .…”
Section: Role Of Tmem16f/ano6 In Volume Regulation and Regulated Cellsupporting
confidence: 77%
“…For ANO6/ TMEM16F, a similar role has been described recently (Juul et al 2014;Ousingsawat et al 2015;Sirianant et al 2015). ANO6 is a Ca 2+ -activated phospholipid scramblase that may also operate as a Ca 2+ -activated Cl − or nonselective ion channel (Grubb et al 2013;Kunzelmann et al 2014;Shimizu et al 2013;Suzuki et al 2010;Tian et al 2012;Yang et al 2012). We found that ANO6 is activated by hypotonic cell swelling, or, alternatively, controls the activity of VRAC .…”
Section: Role Of Tmem16f/ano6 In Volume Regulation and Regulated Cellsupporting
confidence: 77%
“…Ano6 has attracted large attention due to its properties as a Ca 2+ -activated phospholipid scramblase and Ca 2+ -activated Cl − channel (for review see Kunzelmann et al [26]). Despite earlier controversies arguing against the role of Ano6 as a Cl − permeable ion channel [54], it has now been clearly shown by several independent groups, to produce a large conductance Cl − permeable channel activated by strong (≥10 μM) increase in intracellular Ca 2+ [15,21,30,31,46,49]. Moreover, Ano6 has been shown to be activated during cellular volume regulation and apoptotic cell death [1,20,21,31].…”
Section: Discussionmentioning
confidence: 99%
“…Although TMEM16A and TMEM16B are clearly Ca 2+ -activated Cl -channels (Caputo et al, 2008;Schroeder et al, 2008;Yang et al, 2008), the physiological functions of other members of the TMEM16 family have been dubious (Duran and Hartzell, 2011). For example, although TMEM16F certainly is a phospholipid scramblase (Suzuki et al, 2010), it has also been reported to be a nonselective cation channel Adomaviciene et al, 2013) and various types of Cl -channel (Almaç a et al, 2009;Martins et al, 2011;Szteyn et al, 2012;Grubb et al, 2013;Shimizu et al, 2013;Juul et al, 2014). The crystal structure of nhTMEM16 does not reveal an obvious alternative pathway for ion permeation through the bilayer other than the path taken by phospholipids and we have proposed that the ion conductance of TMEM16F represents a leak of ions through the aqueduct that occurs during lipid scrambling (Yu et al, 2015).…”
Section: Mechanisms Of Ion Transportmentioning
confidence: 99%